Targeted Delivery of Paclitaxel Using Folic Acid-Conjugated Nanoliposomes for Enhanced Breast Cancer Therapy - Mir, Mohsen; Yegane, Donya Farzane; Farhadi, Shabnam; Gulnara, Nigmatova; Malika, Ruzibakieva; Zebo, Karamatullayeva; Jamshed, Turdumatov; Alijon, Ulmasov; Latifjonova, Gulnoza; Dilbar, Tuksanova; et al. (Asian Pacific Journal of Cancer Biology, 2026)
Background: Targeted drug delivery systems have gained increasing attention as an effective approach to improve therapeutic efficacy while reducing systemic toxicity in cancer treatment. In this study, folic acid-conjugated nanoliposomes [FA-NLs] were engineered as an active tumor-targeting nanocarrier for the selective delivery of paclitaxel to folate receptor–overexpressing breast cancer cells. Materials and Methods: FA-NLs were prepared using the thin-film hydration technique and loaded with paclitaxel. The nanocarriers were comprehensively characterized by SEM, TEM, and DLS to evaluate morphology, particle size, and zeta potential. Encapsulation efficiency and in vitro drug release were assessed under physiological and acidic conditions. Cytotoxicity, cellular uptake, and apoptosis were analyzed using the MTT assay, fluorescence microscopy, and Annexin V/PI flow cytometry, respectively. Results: The optimized FA-NLs exhibited uniform spherical morphology, nanoscale size (< 210 nm), and favorable surface charge, ensuring colloidal stability. The formulation achieved high drugloading capacity and sustained, pH-responsive release behavior. Compared with free paclitaxel and non-targeted liposomes, FA-NLs significantly enhanced intracellular accumulation and cytotoxic efficacy in MCF-7 cells. Flow cytometric analysis further demonstrated markedly elevated apoptosis induction, confirming improved therapeutic performance. Conclusion: Collectively, FA-conjugated nanoliposomes enabled receptor-mediated targeting, efficient cellular internalization, and controlled intracellular drug release, resulting in superior anticancer activity. These findings underscore the potential of FA-NLs as a promising precision nanomedicine platform for targeted breast cancer therapy.